Developing and evaluating a gamified self-management application for inflammatory bowel disease using the ADDIE model and Sukr framework - Narges Norouzkhani; Somaye Norouzi; Mahbobeh Faramarzi; Ali Bahari; Javad Shokri Shirvani; Saeid Eslami; Hamed Tabesh (BMC Medical Informatics and Decision Making)
Abstract Background The prevalence and chronic nature of Inflammatory Bowel Diseases (IBD) is a significant global concern. As the essential part of treatments approach, patient adherence to treatment protocols and self-management practices are crucial to = IBD management. Healthcare initiatives focused on chronic conditions are strongly needed to consider various aspects of gamification and how it can positively affect self-management. Aim The current cognitive study aims to develop a mobile application to integrate the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design model and elaborate on a gamification design based on the reputable Sukr Wheel framework. Methods The current study uses the ADDIE approach to integrate behavior change strategies derived from the self-management theory using the Sukr Wheel gamification (My IBD Buddy) framework on the Android platform. Results The final evaluation was conducted over 14 days. User satisfaction comprised 22 participants aged 20 to 64, all diagnosed with inflammatory bowel diseases. System usability was measured on a scale ranging from 50 to 100. The average usability score for the entire user group was 80.68, indicating a “good” level of satisfaction among the program users based on the ranking scale. Conclusion “My IBD Buddy” mobile application, equipped with gamification for IBD patients, enhances self-efficacy and self-management.